2022
DOI: 10.1155/2022/1363477
|View full text |Cite
|
Sign up to set email alerts
|

Dry Needling and Antithrombotic Drugs

Abstract: Many clinicians increasingly use dry needling in clinical practice. However, whether patients’ intake of antithrombotic drugs should be considered as a contraindication for dry needling has not been investigated to date. As far as we know, there are no publications in analyzing the intake of antiplatelet or anticoagulant agents in the context of dry needling techniques. A thorough analysis of existing medications and how they may impact various needling approaches may contribute to improved evidence-informed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Recently Munoz et al published a review article about DN and antithrombotic drugs. 16 They conclude antithrombotic medication should not be considered as an absolute contra-indication for DN, however, individual risks should be considered and precautions taken. For DN in deeper muscles or close to major blood vessels, they recommend the use of ultrasound guidance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Munoz et al published a review article about DN and antithrombotic drugs. 16 They conclude antithrombotic medication should not be considered as an absolute contra-indication for DN, however, individual risks should be considered and precautions taken. For DN in deeper muscles or close to major blood vessels, they recommend the use of ultrasound guidance.…”
Section: Discussionmentioning
confidence: 99%
“…15 On the other hand, a recently published review by Munoz et al showed that taking antithrombotic medications should not be considered an absolute contraindication to DN techniques as long as specific DN and individual risks are properly considered. 16 Therefore, the goal of this study is to review the evidence concerning the safety of DN in stroke patients. The review will employ scoping review methodology to systematically examine the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…This is the rst case describing the results of DDN for a patient with extensive muscle tone during early rehabilitation with assessments before, immediately after and one hour after the DDN treatment. Such treatments were for many years typically started only during later rehabilitation, particularly for treatment of pain [5][6] and normal hypertensia [7][8].…”
Section: Discussionmentioning
confidence: 99%